The impact pathway of new quality productive forces on regional green technology innovation: A spatial mediation effect based on intellectual property protection - Kun Cheng; Jianhui Yin; Feiyan Wang; Min Wang (PLoS ONE, 2025)
Against the backdrop of global economic transformation and sustainable development, green technological innovation has become a core driver for enhancing national competitiveness and addressing environmental challenges. With the profound changes in production methods and technological innovation, new quality productive forces (NQPF) have emerged as a key driver of green technological innovation. This study aims to explore the mechanisms through which NQPF influence Regional Green Technology Innovation (RGTI), with a particular focus on the mediating role of intellectual property protection (IPP). Using panel data from 31 provinces in China from 2011 to 2022, we conduct an empirical analysis employing a spatial Durbin model and a spatial mediation effect model. The results indicate that NQPF significantly promote RGTI, particularly in enhancing resource utilization efficiency and greening production processes. However, the study also identifies an inverted U-shaped relationship between NQPF and green technological innovation, primarily driven by local dynamics, where the positive effect diminishes after reaching a certain threshold. Further analysis reveals that IPP plays a crucial mediating role, not only directly fostering green innovation but also amplifying the positive effects of NQPF by enhancing the efficiency of innovation outcomes. Based on these findings, this study offers policy recommendations for promoting RGTI, emphasizing the need to strengthen support for NQPF, improve IPP mechanisms, and build a regional collaborative innovation system.